Efectos de aireación y quimiotropismo inducido durante las fases fenológicas de las plantas de banano (musa × paradisiaca), cultivar williams - Ramirez Loayza, Bryan Steven (Machala : Universidad Técnica de Machala, 2021)
Banana (Musa x paradisiaca L.) is a highly prestigious fruit in Ecuadorian exports, a generator of very important foreign exchange for the country, in addition to its high nutritional value and beneficial contributions to health. In this project, with the use of the herculization technique and application of the 5 established treatments: biochar, compost, biochar + compost, calcium power and control, it is sought to verify with which of these edaphic fertilizers there is better productivity in banana plants (Musa x paradisiaca L.) cultivate Williams and development of the corresponding root system, thanks to the effects of aeration and chemotropism, for which the following specific objectives were set: 1. Establish the effect of aerotropism and induced chemotropism on the root system of the banana plant. 2. Determine the effect of aerotropism and induced chemotropism on agronomic parameters in banana cultivation. 3. Analyze effects on the productivity of banana cultivation of aerotropism and induced chemotropism. The field work was carried out at the Santa Inés Farm, belonging to the Faculty of Agricultural Sciences, of the Technical University of Machala. The study variables considered were: height of daughter plants, foliar emission, number of final leaves with which the plant arrived at calving, grade and leaves at cut, total weight of the harvested bunch, number of hands, weight of the stem (rachis), number of fingers of the hand sol and their degree, also the length of the finger on the hand one and sol, weight of the healthy roots, damaged, with presence of nematodes and dry. As a result, treatment 2 corresponding to compost, allowed to obtain better results, since it is evidenced in the greater presence of the root system including greater weight in healthy roots and less in damaged roots and with the presence of nematodes; this thanks to the fact that the compost contributed to the presence of worms and other microorganisms, which shows a greater amount of micronutrients. Regarding the leaves at harvest, treatment 5, constituted by the control, showed greater resistance to black sigatoka. Among the 5 treatments, number 2 (compost) had the harvest of clusters with the highest weight in pounds, as is the case of 116.1 lb of which its rachis (cluster stem) weighed 13.8 lb, with 9 hands, and a sol hand with 20.2 lb. This plant reached a height of 3.60 m leaving a return of 2.70 m, reaching the calving with 12 completely healthy leaves, and with a time of 21-22 weeks taking into account the beginning of this time when found with a height of 1.61 m (data taken on July 29, 2020), and that the calving time until reaching the harvest of this plant was 12 weeks. Regarding the length of fingers in the banana bunches, what is allowed for export is 7 inches. Emphasizing this, treatment 2, in all the plants to which it was applied, had an average of 9.5 inches in reference to hand one (lower hand), and in the sun hand with an average of 13 inches. With T1, a higher average of hand-sun degrees was obtained. And with the T5 there was a higher average of sun hand fingers.
El banano (Musa x paradisiaca L.) es una fruta de alto prestigio en la exportación ecuatoriana, generador de divisas muy importantes para el país, además de su alto valor nutricional y aportes beneficiosos a la salud. En el presente proyecto, con el uso de la técnica de herculización y aplicación de los 5 tratamientos establecidos: biochar, compost, biochar + compost, power de calcio y testigo, se busca comprobar con cuál de estos fertilizantes edáficos se da una mejor productividad en las plantas de banano (Musa x paradisiaca L.) cultivar Williams y desarrollo del sistema radicular correspondiente, gracias a los efectos de aireación y quimiotropismo, para lo cual se planteó como objetivos específicos los siguientes: 1. Establecer el efecto del aerotropismo y quimiotropismo inducido sobre el sistema radicular de la planta de banano. 2. Determinar el efecto del aerotropismo y quimiotropismo inducido en parámetros agronómicos en el cultivo de banano. 3. Analizar efectos en la productividad del cultivo de banano del aerotropismo y quimiotropismo inducido. El trabajo de campo se llevó a cabo en la Granja Santa Inés, perteneciente a la Facultad de Ciencias Agropecuarias, de la Universidad Técnica de Machala. Las variables de estudio consideradas fueron: altura de las plantas hijas, la emisión foliar, número de hojas final con el que llegó la planta a la parición, grado y hojas al corte, peso total del racimo cosechado, número de manos, peso del tallo (raquis), número de dedos mano sol y su grado, también la longitud del dedo en la mano uno y sol, peso de las raíces sanas, dañadas, con presencia de nemátodos y secas. Como resultado, el tratamiento 2 correspondiente al compost, permitió obtener mejores resultados, puesto que se evidencia en la mayor presencia del sistema radicular incluyendo mayor peso en raíces sanas y menor de raíces dañadas y con presencia de nemátodos; esto gracias a que el compost contribuyó a la presencia de lombrices y demás microorganismos, lo que evidencia mayor cantidad de micronutrientes. En cuanto a las hojas a la cosecha, el tratamiento 5, constituido por el testigo, presentaron mayor resistencia a la sigatoka negra. De entre los 5 tratamientos, el número 2 (compost) contó con la cosecha de racimos con mayor peso en libras, como es el caso de 116,1 lb del cual su raquis (tallo de racimo) pesó 13,8 lb, con 9 manos, y una mano sol con 20,2 lb. Esta planta llegó a tener una altura de 3,60 m dejando un retorno de 2,70 m, llegando a la parición con 12 hojas completamente sanas, y con un tiempo de 21-22 semanas tomando en consideración el inicio de este tiempo cuando se encontraba con una altura de 1,61 m (dato tomado el 29 de julio del 2020), y que el tiempo de parición hasta llegar a la cosecha de esta planta fue de 12 semanas. En cuanto a la longitud de dedos en los racimos de banano, lo permitido para exportación, es de 7 pulgadas. Haciendo énfasis en esto, el tratamiento 2, en todas las plantas a las que se les aplicó, tuvieron un promedio de 9,3 pulgadas en referencia a la mano uno (mano bajera), y en mano sol con un promedio de 12,8 pulgadas. Con el T1 se obtuvo mayor promedio de grados mano sol. Y con el T5 se presentó mayor promedio de dedos mano sol.
Keywords: HERCULIZACIÓN; AIREACIÓN; QUIMIOTROPISMO; BANANO